Development of ADPS «Assessment of investment attractiveness of agrarian enterprises» - Білоусова, М. М. (Scientific Progress & Innovations, 2012)
A procedure for assessing the investment attractiveness of enterprises was proposed, an automated data processing system «Assessment of investment attractiveness of agrarian enterprises» was developed. Designing the database tables and relationships between them was carried out using database Microsoft SQL Server, as the chosen programming language C #. Application of the proposed program will enable managers to make management decisions in the field of improving the investment attractiveness of enterprises quickly and accurately.